Inguinal hernia of the distal ureter causing hydronephrosis: A rare case - Smith, Matthew T. (Urol Case Rep, 2020)
Ureteral involvement in inguinal hernias is a rare occurrence. A 63-year-old man presented for surveillance of renal cell carcinoma with new onset mild intermittent flank pain. CT scan revealed new left hydroureteronephrosis to the level of the inguinal canal with dilated segments of ureter within an inguinal hernia. The patient underwent robot-assisted laparoscopic left ureterolysis and hernia repair. Ureter-containing inguinal hernias represent an uncommon but important source of obstructive uropathy. When encountered, robotic hernia repair provides a safe and effective treatment option.